Adherence Population to Vaccination of Influenza: Survey Results - T. A. Bayanova; A. G. Petrova; A. S. Vanyarkina; N. Yu. Kupriyanova; T. A. Gavrilova (Эпидемиология и вакцинопрофилактика, 2021)
Influenza remains one of the most pressing medical and socio-economic problems . Vaccination is the most effective way to reduce the incidence and mortality of influenza and its complications. Рurpose: estimate the awareness of parents , doctors of various specialties and students of the medical University about the issues of influenza vaccination, identify factors that affect the reduction of vaccination adherence and determine the best apt ways to increase adherence to influenza immunoprophylaxis. Methods. A descriptive retrospective epidemiological study between 2004 and 2018 Conducted a survey among three groups of respondents: parents of children enrolled in the children's clinic or treated at a pediatric hospital (n=1620); doctors of different specialties (n = 324); the medical students (n = 433). Resalts. Against the background of increasing coverage of the population with preventive vaccinations, there is a decrease in the incidence of influenza among the total population (TPR.=-14.7%). There was a weak correlation between the number of vaccinated and the incidence in the following year (ρ =-0.38 p>0.05). Only 22.2% of respondents vaccinate a child, and only adults are vaccinated in 13.8% of cases. Among doctors of different specialties, 36.7% are vaccinated against the flu, and 58.7% of respondents additionally vaccinate their children against the flu. Of the total number of students surveyed, 17.3% are vaccinated annually. Conclusions. Increasing adherence to flu vaccination among medical students and doctors will help increase adherence to vaccination among the population, increase coverage of preventive vaccinations, and reduce the incidence of influenza.